Extraction Optimization and Characterization of Collagen from Yellow Pike Conger Swimbladder with Acid-Hydro-Exctraction Method - Fernandy Djailani; Win Trilaksani; Tati Nurhayati (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Swim bladder is one of marine potential byproducts for alternative source of collagen. This study aimedto optimize hydro-extraction and characterized collagen. Extraction optimization of collagen was determinedusing Box-behnken design response surface method with three variables: CH3COOH concentration, soakingtime and extraction time to yield response. Hydro-extraction collagen was characterization based on theamino acid content, SDS-PAGE, FT-IR and DSC. Acording to the result, the concentration had significantlyinfluence yield. Optimum extraction conditions were variable combinations of acetic acid concentration of0.1 M, for 1 h and hydro-extraction time of 1 h to produce the highest yield 63.35%. collagen was classifiedas type I collagen by amino acid content, electrophoresis patterns and fourier transform infrared (FTIR)spectra. The glass transition of collagen was 67.23oC, showed high thermal stability that can be applied tothe cosmetics industry and nutraceutical.